P597 Comparison of assays and specimen types for the diagnosis of mycoplasma genitalium and macrolide resistant mutations. (14th July 2019) - Chernesky, Max; Jang, Dan; Martin, Irene; Shah, Anika; Smieja, Marek; Speicher, David; Clavio, Avery; Arias, Manuel
Abstract : Background: The Aptima MG assay (Hologic Inc.) detects Mycoplasma genitalium (MG). SpeeDx Resistance Plus MG (SpeeDx Pty Ltd) simultaneously determines whether the MG detected is a wild-type (WT) or has any of 5 macrolide resistant mutations (MRM) in the 23S rRNA gene. The STD6 ACE assay (Seegene Canada Inc.) which is Health Canada approved and Aptima require further testing for MRM by 23S rRNA sequencing. The objectives were to enroll 300 women to self-collect 3 vaginal swabs (VS) and first-void urine (FVU) to be tested for MG in the 3 assays and for MRM. Methods: Aptima was performed on a Panther instrument. STD6 ACE used EasyMag extraction and gel electrophoresis. SpeeDx was extracted on an m2000sp and amplification was on an ABi 7500. Positives from Aptima and STD6 were tested for MRM by sequence typing. Extra positives by Aptima were blindly tested with negatives by alternate assays, detecting distinctly different 16S rRNA and 23S rRNA. Agreements and Kappa values were calculated for MG detection and MRM. Results: For 190 women, MG-positives by SpeeDX were 24 VS and 17 FVU, compared to 17 VS and 9 FVU by STD6. Aptima detected 34 VS and 29 FVU as positive. Overall agreements and Kappa values were very good K 0.82 (VS) to good K 0.69 (FVU) between Aptima and SpeeDx, but moderate to fair for Aptima or SpeeDx with STD6. Confirmatory testing of extra positives confirmed 79% (11/14) as positive for Aptima and 0% (0/6) for STD6. Patient MRM rates from each assay were 60% (15/25) SpeeDx, 63.6% (7/11) Aptima and 57.9% (11/19) STD6. Conclusion: Aptima was more sensitive on both VS and FVU. VS was a better sample than FVU for SpeeDx. STD6 lacked sensitivity and specificity for the identification of MG.MRM rates were similar for the three identification and typing systems. Disclosure: No significant relationships.